Aggravated nausea and vomiting induced by fat emulsion for hyperemesis gravidarum: A case report. (5th May 2017) - Zhao, B.; Li, M.; Ren, C.; Liu, X. Y.; Mei, D.
Summary: What is known and objective: Total parental nutrition (TPN) for hyperemesis gravidarum (HG) is generally effective and well‐tolerated. We report a case of aggravated nausea and vomiting caused by fat emulsion. Case description: A 40‐year‐old pregnant woman through IVF was admitted to the hospital at 11‐week gestation and diagnosed with HG. During TPN treatment, the patient suffered from aggravated nausea and vomiting. We identified fat emulsion as the most likely culprit using challenge, dechallenge and rechallenge. What is new and conclusion: This is the first report of fat emulsion aggravating nausea and vomiting in such situation. Abstract : We report a case of aggravated nausea and vomiting after TPN treatment for HG. The patient was sensitive on different kinds of fat emulsion, and we also use the adverse reaction criteria to describe the challenge, de‐challenge and re‐challenge process to identify fat emulsion as the culprit.